A meta-analysis of satisfaction in marketing channel relationships - GEYSKENS, Inge (Institutional Knowledge at Singapore Management University, 1999)
The authors advance a conceptual model of channel member satisfaction that distinguishes between economic and noneconomic satisfaction. The resulting model then is tested using meta-analysis, Meta-analysis enables the empirical investigation of a model involving several constructs that never have been examined simultaneously within an individual study. More specifically, the authors unify the stream of research on power use-the focus of many satisfaction studies in the 1970s and 1980s-with more recent work on trust and commitment, which usually explores antecedents other than power use. The results indicate that economic satisfaction and noneconomic satisfaction are distinct constructs with differential relationships to various antecedents and consequences. Furthermore, this study demonstrates that satisfaction is both conceptually and empirically separable from the related constructs of trust and commitment.